FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT SISWA MEMILIH SEKOLAH DI SMA NURIS JEMBER - Weni Kurnia Rahmawati; Abdurrahman Ahmad (Jurnal Bimbingan dan Konseling Terapan, 2019)
The interest of students to enter in high school is important because it also encourages schools to continue to improve their quality so as to create good relationships between schools, graduates, stakeholders, and parents of students. This study aims to determine the factors that influence student interest in school at Nurul Islam Jember High School. This research is a descriptive research. The sampling technique is quota sampling. The data analysis technique uses factor analysis. The results of the study show that the Kaiser-Meyer-Olkin value Measure of Sampling Adequacy is greater than 0.50 which is equal to 0.721> 0.50 and the value of Barlett’s Test of Sphericity (Sig.) 0,000 <0.05. The MSA value for the variable under study is greater than 0.50 except for the variable q26 or question number 26 where the value of MSA is 0.375 <0.50 so that this variable is not used. the conclusions of the study are the factors that influence students choosing schools in Nurul Islam Jember High School consisting of 25 variables grouped into 7 factors. The first factor was the influence of parents with Initial Eigenvalues of 5.131, Peers with Initial Eigenvalues 4.185, Academic Success with Initial Eigenvalues 2,899, Early school experience with Initial Eigenvalues 1,563, Attitudes toward work with Initial Eigenvalues 1,284, Relations between teachers and students with Initial Eigenvalues 1,140, The emotional atmosphere of the school with Initial Eigenvalues 1.110. Suggestions for research are so that further research can measure the influence of each variable.